Pengembangan Aplikasi Resep Masakan dengan Rekomendasi berdasarkan Bahan-Bahan Makanan Berbasis Web - Wunsel Arto Negoro; Faizatul Amalia; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cooking is a way to process food ingredients and seasonings to be a variety of dishes. While cooking, we need recipes as a guide to processs food ingredients into a dish. Cooking some food is a solution to solve the problem of saving money for college students. However, in reality there are many college students who have difficulty in determining what kind of food they can make based on food ingredients they already have. Based on this case, author developed an application of cooking recipes with recommendation of web-based food ingredients. To get recipe recommendations, author needs cosine similarity method to compare food ingredients that have been owned with recommended recipes. The process of system development uses the waterfall method. The developed system gets 31 functional requirements and 1 non-functional requirement. Functional requirements were tested by validation testing and unit testing with 100% valid results. Non-funtional requirement was tested by compatibility testing with the results of 2 critical issues on firefox and chrome browsers. The recipe recommendation was tested by precision and recall testing with the average precision value 0.65 and the average recall value 0.19. The development of cooking recipes application with recommendation of web-based food ingredients, is expected to help college students to process food ingredients into a dish.